POLYPOIDAL CHOROIDAL VASCULOPATHY FEATURES VARY ACCORDING TO SUBFOVEAL CHOROIDAL THICKNESS. Issue 5 (May 2021) - Jordan-Yu, Janice Marie; Teo, Kelvin Yi Chong; Chakravarthy, Usha; Gan, Alfred; Tan, Anna Cheng Sim; Cheong, Kai Xiong; Wong, Tien Yin; Cheung, Chui Ming Gemmy
Abstract : Purpose: To evaluate associations between choroidal thickness and features of polypoidal choroidal vasculopathy (PCV) lesions based on multimodal imaging. Methods: This cross-sectional analysis included treatment-naive PCV eyes from a prospectively recruited observational cohort. Associations between of subfoveal choroidal thickness (SFCT) and qualitative and quantitative morphologic features of PCV lesions on color fundus photographs, indocyanine green and fluorescein angiography, and spectral-domain optical coherence tomography were evaluated. Results: We included 100 eyes with indocyanine green angiography–proven PCV. Subfoveal choroidal thickness showed a bimodal distribution with peaks at 170 µ m and 350 µ m. There was a significant linear increase in the total lesion area ( P -trend = 0.028) and the polypoidal lesion area ( P -trend = 0.030 and P -continuous = 0.037) with increasing SFCT. Pairwise comparisons between quartiles showed that the total lesion area (4.20 ± 2.61 vs. 2.89 ± 1.43 mm 2, P = 0.024) and the polypoidal lesion area (1.03 ± 1.01 vs. 0.59 ± 0.45 mm 2, P = 0.042) are significantly larger in eyes in Q4 (SFCT ≥ 350 μ m) than eyes in Q1 (SFCT ⩽ 170 μ m). Although there was no significant linear trend relating SFCT to best-corrected visual acuity, pairwise comparisons showed that eyes in Q4 (SFCT ≥ 350 μ m) have significantly worse vision (0.85 ± 0.63 vs. 0.55 ± 0.27 logMAR, P = 0.030) than eyes in Q2 (SFCT 170–260 μ m). Conclusion: Total lesion areas and polypoidal lesion areas tend to be larger in eyes with increasing SFCT. Choroidal background may influence the phenotype or progression pattern of PCV. Abstract : Polypoidal choroidal vasculopathy features vary according to subfoveal choroidal thickness. Thicker choroid is associated with a larger polypoidal choroidal vasculopathy lesion area and a larger polypoidal lesion area. Choroidal morphology may influence the phenotype and/or progression of the polypoidal choroidal vasculopathy complex.